(untitled) (NAU Journal of Library and Information Science, 2024)
This study primarily examined lecturers’ awareness and attitude as predictors of institutional repository usage in Landmark University, Omu-aran, Kwara State. Descriptive survey research design was adopted and a sample of 308lecturers were selected by using total enumeration sampling technique. A self-designed questionnaire was used to collect data from 308 respondents, of which 272 copies were returned and completely filled. Frequency counts and percentages were used to analyze the data collected for the four research questions while PPMC was used to test the two null hypotheses of the study. The study found that the level of awareness of the lecturers about IRs is high, and they hold positive attitudes toward IRS. The results further showed that the majority of the respondents use IRs to a great extent while inadequate content submission; poor internet network; and epileptic power supply are the major challenges associated with the use of IRs among the lecturers. The results of the first hypothesis showed a significant relationship between awareness and utilization of IRs among the lecturers. Furthermore, the results of the second hypothesis showed a significant relationship between attitudes and utilization of IRs among the lecturers. The study recommends that university management should offer sessions to familiarize lecturers with the repository’s features, the benefits of open access, and how to deposit their works. Also, the university authority should provide clear information about copyright policies, permissions, and options for uploading pre-prints or post-prints.